Perancangan Sistem Informasi E-report Berbasis Web Menggunakan PHP dan MySQL pada Divisi Quality Control PT. Kraktau Baja Kontruksi - Fikri Pirmansyah; Djamaludin; Ajrina Febri Suahati (Bandung Conference Series: Industrial Engineering Science, 2024)
Abstract. This research was conducted at a profiled steel mill in the Quality Control (QC) division. This division is responsible for conducting product inspections in three stages: First stage, dimensional inspection includes measurement of length, width, tolerance, and weight of steel. Second stage, re-dimensional inspection to compare the results of the first dimensional inspection. The third stage, marking inspection (visual) which includes marking, classifying, and determining grade according to steel quality. The current problem in the QC division is that the inspection reports carried out by QC employees still use manual methods in recording and reporting. This causes problems, namely important documents that are scattered and piled up among large unorganized archives. In addition, there is a loss of documents due to the absence of a backup report (report backup), as well as the absence of a special database to store and manage these documents. The purpose of this research is to propose an information system design to facilitate the QC division in the process of inspection reporting, management, and digital data storage on one platform. The result of this research design is a web-based e-report application according to the needs of the QC division. The main features of this application include: login features for access security and user authentication, user registration to manage access rights, inspection data input to record inspection results, shift scheduling to manage employee work schedules, and SOPs to guide the inspection process. System testing using the Black Box Testing method shows that all features function properly and there is no bug or error in the system. Abstrak. Penelitian ini dilakukan di pabrik baja profil bagian divisi Quality Control (QC). Divisi ini bertanggung jawab melakukan inspeksi produk dalam tiga tahapan: Tahap pertama, inspeksi dimensi meliputi pengukuran panjang, lebar, toleransi, dan berat baja. Tahap kedua, inspeksi dimensi ulang untuk membandingkan hasil inspeksi dimensi pertama. Tahap ketiga, inspeksi penandaan (visual) yang meliputi pemberian tanda, pengklasifikasian, dan penentuan grade sesuai mutu baja. Permasalahan saat ini pada divisi QC adalah laporan hasil inspeksi yang dilakukan oleh karyawan QC masih menggunakan metode manual dalam pencatatan maupun pelaporan. Hal ini menyebabkan masalah, yaitu dokumen penting yang tersebar dan menumpuk di antara arsip besar tidak terorganisir. Selain itu, terjadi kehilangan dokumen karena tidak adanya laporan cadangan (report backup), serta tidak adanya database khusus untuk menyimpan dan mengelola dokumen tersebut. Tujuan penelitian ini adalah memberikan usulan rancangan sistem informasi untuk memudahkan divisi QC dalam proses pelaporan inspeksi, pengelolaan, dan penyimpanan data secara digital dalam satu platform. Hasil perancangan penelitian ini adalah sebuah aplikasi e-report berbasis web sesuai dengan kebutuhan divisi QC. Fitur-fitur utama dari aplikasi ini diantanya: fitur login untuk keamanan akses dan autentikasi pengguna, registrasi pengguna untuk mengatur hak akses, input data inspeksi untuk mencatat hasil pemeriksaan, penjadwalan shift untuk mengatur jadwal kerja karyawan, dan SOP untuk panduan proses inspeksi. Pengujian sistem menggunakan metode Black Box Testing menunjukkan bahwa semua fitur berfungsi dengan baik dan tidak adanya sebuah bug ataupun kesalahan pada sistem.